Analisis Penerapan ISO 9001 : 2015 Di Perusahaan Manufaktur Produksi Sepatu - Paolinus Hulu; Arif Maulana; Firman Fahriz (Journal of Information Systems and Management (JISMA), 2023)
Today's developments have a competitive impact on the manufacturing and service industries, thus encouraging companies to optimize their strategies. This research is an integration of Lean Thinking with international standards based on ISO 9001: 2015 in shoe companies. The method of writing this article is a narrative literature review of 3 (three) articles that discuss the analysis of the implementation of ISO 9001: 2015 which aims to identify and summarize previously published articles without any criticism for the articles being reviewed. The results of the review show that several factories producing shoes carry out quality improvements, performance improvements, and risk implementation on an ongoing basis so as to minimize and reduce the impact of these risks. as well as being able to determine the mitigation steps in advance in order to maintain product quality with the standard indicator of the assessment being ISO 9001: 2015 Quality Management System (QMS) certification. The data used in this study are in the form of the company's existing conditions, internal issues and external issues, as well as ISO 9001:2015 requirements. Based on the results of the risk register, there are 4 risks that have a medium and high level, 4 risks that require action will be given a risk treatment plan in the form of a mitigation plan and contingency planning, but risks that have a high level will be designed. In this study the risk that will be designed to handle is the delay in purchasing materials that have a high level of risk, the design that will be carried out is in the form of an SOP. SOP has considered the list of risks and gap analysis results.